Earthworm, suborder Crassiclitellata, cohort Terrimegadrili (Jamieson, 1988): EENY-532/IN946, 9/2012 - Crow, William T. (EDIS, 2012)
Like insects, earthworms are among the animals most frequently encountered by many Floridians. Our kids play with them, dissect them in middle school biology, we fish with them, they crawl across our sidewalks and live in our flowerpots. Despite this, their ecological and economic importance often goes unrecognized. Earthworms have several important ecological roles. Additionally, some species are used commercially for bait, animal feed, environmental remediation, and composting. This 6-page fact sheet was written by William T. Crow and published by the UF Department of Entomology and Nematology, September 2012. EENY-532/IN946: Earthworm, suborder Crassiclitellata, cohort Terrimegadrili (Jamieson 1988) (ufl.edu)